Confidence and Attitudes Toward Osteoarthritis Care Among the Current and Emerging Health Workforce: A Multinational Interprofessional Study. Issue 4 (22nd May 2019) - Briggs, Andrew M.; Hinman, Rana S.; Darlow, Ben; Bennell, Kim L.; Leech, Michelle; Pizzari, Tania; Greig, Alison M.; MacKay, Crystal; Bendrups, Andrea; Larmer, Peter J.; Francis‐Cracknell, Alison; Houlding, Elizabeth; et al.
Abstract : Objective: To measure confidence and attitudes of the current and emerging interprofessional workforce concerning osteoarthritis (OA) care. Methods: Study design is a multinational (Australia, New Zealand, Canada) cross‐sectional survey of clinicians (general practitioners [GPs], GP registrars, primary care nurses, and physiotherapists) and final‐year medical and physiotherapy students. GPs and GP registrars were only sampled in Australia/New Zealand and Australia, respectively. The study outcomes are as follows: confidence in OA knowledge and skills (customized instrument), biomedical attitudes to care (Pain Attitudes Beliefs Scale [PABS]), attitudes toward high‐ and low‐value care (customized items), attitudes toward exercise/physical activity (free‐text responses). Results: A total of 1886 clinicians and 1161 students responded. Although a number of interprofessional differences were identified, confidence in OA knowledge and skills was consistently greatest among physiotherapists and lowest among nurses (eg, the mean difference [95% confidence interval (CI)] for physiotherapist‐nurse analyses were 9.3 [7.7‐10.9] for knowledge [scale: 11‐55] and 14.6 [12.3‐17.0] for skills [scale: 16‐80]). Similarly, biomedical attitudes were stronger in nurses compared with physiotherapists (6.9 [5.3‐8.4]; scale 10‐60) and in medical students compared with physiotherapy students (2.0 [1.3‐2.7]). Some clinicians and students agreed that people with OA will ultimately require total joint replacement (7%‐19% and 19%‐22%, respectively), that arthroscopy is an appropriate intervention for knee OA (18%‐36% and 35%‐44%), and that magnetic resonance imaging is informative for diagnosis and clinical management of hip/knee OA (8%‐61% and 21%‐52%). Most agreed (90%‐98% and 92%‐97%) that exercise is indicated and strongly supported by qualitative data. Conclusion: Workforce capacity building that de‐emphasizes biomedical management and promotes high‐value first‐line care options is needed. Knowledge and skills among physiotherapists support leadership roles in OA care for this discipline.